“NGELEBENGANG” TRADISI PEMBUATAN GULA AREN DESA PEDAWA DALAM FOTOGRAFI STORY - Pranata, Gusti Putu Richie Efendi; Nindhia, Cokorda Istri Puspawati; Adityasmara, Farhan (Retina Jurnal Fotografi, 2021)
Palm sugar is sugar made from sap or palm tree juice. Most people prefer palm sugar because it is considered more fragrant, tasty and clean. Pedawa Village is a village that still maintains the tradition of making palm sugar known as "Ngelebengang". Palm sugar made by the people of Pedawa Village has clean characteristics, a sweet taste and quite strong resistance to hot temperatures which is the result of the unique process of making sugar by using facilities such as waluh, dadap wood and mangosteen leaves. This uniqueness gives the idea to make Pedawa Village palm sugar as an object in making story photography work with the aim of visualizing the process of making Pedawa Village palm sugar into photographic media in order to provide additional insight for writers and increase knowledge about the Ngelebengang process for the community. The creator applies the observation method regarding palm sugar in Pedawa Village by collecting data through website sources, journals and books and conducting direct interviews. In addition, the creator also uses EDFAT theory and aesthetic theory in the process of creating photo works. After the shooting process, the best photo selection stage is carried out which is continued to the image processing stage to the final stage of the creation process, namely the exhibition. As a result of the creation of this final project, the creator gets 15 pictures from visualization of the Ngelebengang tradition through a series of activities that have existed for generations in Pedawa Village to maintain ancestral traditions. In the process of shooting, the creator applies several photography techniques, including stop action, framing and the application of lighting exposure through the use of an external flash. Keywords : Ngelebengang, Palm Sugar, Pedawa Village, Story Photography